(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Complex sentence structures serve a fundamental function in human communication, particularly in academic, literary, and official discourses. Their importance becomes even more pronounced when examining how various languages express nuanced relationships between actions, events, and conditions. Among the many types of complex sentences, causal, consequential, conditional, and temporal constructions occupy a central place, as they enable speakers and writers to precisely articulate reasons, results, hypotheses, and sequences of actions. A comparative analysis of these sentence types, especially within the context of English and Uzbek, reveals not only cross-linguistic similarities but also the unique ways in which languages map human experience onto grammatical structures.